Isolated cerebellar nodulus infarction: Two case reports and literature review. (July 2021) - Toudou-Daouda, Moussa; Alecu, Cosmin; Chausson, Nicolas; Aminou-Tassiou, Nana Rahamatou; Smadja, Léonard; Soumah, Djibril; Aghasaryan, Manvel; Al Tarcha, Tony; Smadja, Didier
Highlights: ICNI has great clinical similarity with APV, from which it is difficult to distinguish. The discriminant clinical elements that differentiate ICNI from APV were direction-changing GEN, bilateral lateropulsion/fall on Romberg's test, and normal h-HIT. We add one more clinical discriminant element that can helpful for the neurologist for the diagnosis. MRI is the sole examination that can allow to bring out the infarction of the cerebellar nodulus. Abstract: Background: Isolated cerebellar nodulus infarction (ICNI) is rare and has great clinical similarity with acute peripheral vestibulopathy (APV), from which it is difficult to distinguish. We report two cases of ICNI followed by a literature review to identify the discriminant clinical elements that differentiate ICNI from APV. Methods: We describe in detail our 2 cases. Besides, a literature search in Medline via PubMed and Scopus was performed up to May 17, 2020. Clinical characteristics, mainly of well-described cases, were extracted and analyzed. Results: Our search yielded 43 total publications, among which 13 were selected, including 23 patients. Spontaneous or positional rotatory vertigo with unidirectional spontaneous horizontal nystagmus, associated with the postural imbalance and unilateral lateropulsion or fall on Romberg's test, was the most common clinical picture. According to our literature review, the discriminant clinical elements which differentiate ICNI from APV were direction-changing gaze-evoked nystagmus, bilateral lateropulsion or fall on Romberg's test, and normal horizontal head impulse test. Our two patients reported a positional fleeting abnormal visual perception of spatial orientation of objects. We proposed this symptom as a discriminant clinical element. Conclusion: The ICNI constitutes a difficult differential diagnosis of APV. Through our two patients reported here, we proposed a supplementary discriminant symptom helpful for the clinical diagnosis.